Modeling and experimental study condenser performance of fixed bed pyrolysis reactor: A case study of solid waste palm starch processing - Herman Saputro; Laila Fitriana; Aris Purwanto; Alan Firdaus; Riyadi Muslim; Fudhail A. Munir; Wei-Cheng Wang (Cleaner Engineering and Technology, 2023)
Sustainable management of vermicelli waste can reduce waste in the environment. In addition, this waste can be used as a renewable fuel source. This study researched the condenser performance concerning the pyrolysis process of biomass from palm starch waste. The solid waste of palm starch was collected from the traditional industry of vermicelli noodles in Klaten District, Indonesia. The solid waste of palm starch formed into RDF-5 biomass. In this research, we use numerical and experimental methods to obtain a performance model of a pyrolysis condenser. The numerical simulation and experiment used different variations of tube models and fluid flow directions. The numerical simulation results show that the helical tube performs better than the concentric tube regarding heat transfer rate and LMTD value. After getting the numerical result, we were going to experiment with three different helical coil-type condenser pipe diameters in the Fixed bed pyrolysis reactor. Based on the experimental results, the condenser with the smallest diameter and parallel flow direction has higher liquid smoke with 41.802% yield production. The pyrolysis of palm starch waste can reduce environmental waste and turn the waste into liquid smoke. However, before it can be used as a bio-diesel additive, the liquid smoke in this research needs to be processed further.